2021
DOI: 10.1200/go.20.00625
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Newly Diagnosed Multiple Myeloma at a Tertiary Care Center in North India (IMAGe: 001A Study)

Abstract: PURPOSE The outcomes of patients with myeloma from developing countries are often lacking because of poor record maintenance. Publications from such settings are also limited because of the retrospective nature of the data collection. Information technology can bridge these gaps in developing countries with real-time data maintenance. We present the real-time survival data of the patients with myeloma from a tertiary care center in North India using one such indigenously built software. PATIENTS AND METHODS Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
1
3
1
Order By: Relevance
“…Contrary to our study findings, MM is globally known to predominantly affect African males [ 5 , 7 , 9 , 14 , 33 , 34 ]. In 2009, another South African study by Rankapole et al, found a similarly higher proportion of females with MM and the South African National Institute of Communicable Diseases National Cancer Registry, also recorded an increasing incidence of MM in African females from 2016–2018 [ 6 , 14 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our study findings, MM is globally known to predominantly affect African males [ 5 , 7 , 9 , 14 , 33 , 34 ]. In 2009, another South African study by Rankapole et al, found a similarly higher proportion of females with MM and the South African National Institute of Communicable Diseases National Cancer Registry, also recorded an increasing incidence of MM in African females from 2016–2018 [ 6 , 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Anaemia is reportedly the most common presenting complaint in MM, and this concurred with our laboratory findings [ 7 , 33 , 48 ]. However, patients predominantly complained of bone pain rather than symptoms of anaemia, upon presentation to hospital.…”
Section: Discussionsupporting
confidence: 91%
“…MM is more common in elderly individuals; patients in this age group often suffer from other comorbidities such as diabetes and dyslipidemia [ 4 , 5 , 6 ]. Over 1 in 4 patients with MM has diabetes and 29.3% of myeloma patients have dyslipidemia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor (PPAR) agonists are U.S. Food and Drug Administration (FDA)-approved drugs indicated for use in type 2 diabetes and dyslipidemia [ 8 , 9 ]. Both the comorbidities and their treatment can have a severe impact on patients or can severely interact with the natural biology of MM [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MCN was present in 86.6% of the patients with severe AKI (4). Around 50 % to 60% of MM patients with renal impairment have complete renal recovery (5) and overall survival of MM patients is related with the extent of renal recovery (5,6). With the introduction of bortezomib based chemotherapy there is improved overall survival and renal function in MM (7).…”
Section: Introductionmentioning
confidence: 99%